2016
DOI: 10.1371/journal.pone.0155771
|View full text |Cite
|
Sign up to set email alerts
|

Ani9, A Novel Potent Small-Molecule ANO1 Inhibitor with Negligible Effect on ANO2

Abstract: Anoctamin1 (ANO1)/transmembrane protein 16A (TMEM16A), a calcium-activated chloride channel (CaCC), is involved in many physiological functions such as fluid secretion, smooth muscle contraction, nociception and cancer progression. To date, only a few ANO1 inhibitors have been described, and these have low potency and selectivity for ANO1. Here, we performed a high-throughput screening to identify highly potent and selective small molecule inhibitors of ANO1. Three novel ANO1 inhibitors were discovered from sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 43 publications
4
133
0
Order By: Relevance
“…Recently, Seo et al (2016) identified a new inhibitor, Ani9 that seems to mainly inhibit TMEM16A current with negligible effects on CFTR, VRAC and TMEM16B.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Seo et al (2016) identified a new inhibitor, Ani9 that seems to mainly inhibit TMEM16A current with negligible effects on CFTR, VRAC and TMEM16B.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as described previously [18]. FRT and PC-3 cells were lysed with cell lysis buffer (50 mM Tris-HCl (pH 7.4), 1% Nonidet P-40, 0.25% sodium deoxycholate, 150 mM NaCl, 1 mM EDTA, 1 mM Na 3 VO 4 , and protease inhibitor mixture).…”
Section: Methodsmentioning
confidence: 99%
“…To date, few ANO1 inhibitors have been identified, such as CaCC inh -A01 (IC 50 ~1 μM), tannic acid (IC 50 ~6 μM), T16A inh -A01 (IC 50 ~1 μM), MONNA (IC 50 ~1 μM) and idebenone (IC 50 ~9 μM) [1317], and more recently we identified a novel small-molecule inhibitor of ANO1, Ani9 (IC 50 ~77 nM), showing high potency and selectivity for ANO1 [18]. However, the mechanisms of action and pharmacological properties of these inhibitors remain unclear, and the ANO1 inhibitors are still in the early phases of the drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…TMEM16A and TMEM16B are also blocked by other commonly used Cl À channel blockers such as 4,4 0 -diisothiocyano-2,2 0 -stilbenedisulfonic acid (DIDS) and niflumic acid with comparable potencies (Bradley et al, 2014;Liu et al, 2015;Pifferi et al, 2009). In contrast, a recently identified drug (Ani9) selectively inhibited TMEM16A, with no significant block of TMEM16B (Seo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%